Pemberian Sereal Instan Calissa (Pisang, Sorgum, Kacang Almond) dalam Penurunan Tekanan Darah Penderita Hipertensi di Puskesmas Sukarami Palembang - Susyani, Susyani; Pradini, Viska Amalia; Terati, Terati (JGK: Jurnal Gizi dan Kesehatan, 2024)
Background: Hypertension is a medical condition characterized by an increase in systolic blood pressure> 140 mmHg and diastolic blood pressure> 90 mmHg on two measurements with an interval of five minutes in a state of rest / calm. Purpose: This study aims to determine the effect of giving Calissa Instant Cereal on Blood Pressure Reduction in Hypertension Patients in the Sukarami Health Center, Palembang. Methods: This study was a two-stage study consisting of a completely randomized non-faculty and quasi-experimental study with pre-test and post-test research designs with control group design. The study was conducted from January to March 2021. The number of samples was 30 people in the treatment group and 30 people from the comparison group who were taken by means of systematic random sampling. Results: The same number of respondents in the study were male and female (50%), with age> 50 years (50%) with normal nutritional status (53.3%). The mean reduction in blood pressure was 16.87 mmHg systolic and 12.27 mmHg diastolic. The results of statistical tests (t-dependent test) showed that there was an effect of giving calissa instant cereal on reducing blood pressure in hypertensive patients in the working area of ​​the Puskesmas Sukarami Palembang (p = 0.000). Conclusion: Calissa Instant Cereal has an effect on lowering blood pressure in hypertensive patients in the working area of ​​the Sukarami Health Center, Palembang.